Breath-Body-Self : an exploration of the body as a site for generating images for performance making - Matchett, Sara (Department of Drama, 2017)
This thesis investigates the body as a site for generating images for purposes of performance making. It is a methodological study that draws from various traditions, methods and somatic practices, such as yoga, Fitzmaurice Voicework®, the Sanskrit system of rasa, body mapping and free writing. The study specifically focuses on interrogating the relationship between breath and emotion, and breath and image, in an attempt to make performance that is inspired by a biography of the body. It explores the relationship between body, breath and feeling and how this impacts on the imagination in processes of generating images for performance making. It further investigates whether breath can be experienced as an embodied element that is sensed somatically by performers, and in so doing act as a catalyst for activating memories, stories, and experiences held in the body of the performer. The potential of breath as impulse as well as thread that connects imagination, memory, body, and expression, is investigated. Using the conceptual framework of somaesthetics, the study draws from theories of the body, neuroscience and cognitive philosophy to support its claims. Through the disciplinary framework of somaesthetics, as an embodied philosophical practice, it is suggested that the performer cultivates a heightened awareness that makes possible what is being proposed as a process of performance making. It draws on my experience as a lecturer of theatre in the Department of Drama at the University of Cape Town as well as on my experience as a maker of performance with The Mothertongue Project, a women's arts collective I co-founded in South Africa in 2000. My work with The Mothertongue Project, emanates from a particular ideological position in the world that is informed by the context in which I locate. South Africa has some of the highest rates of rape and sexualised violence against women in the world. The result is a society where women's bodies, in particular, are constantly under threat of being violated. In summary, this thesis explores the relationship between a particular kind of performance making process for a particular kind of work within a particular kind of context. It seeks to provide women with the tools and space to speak back to the social context they inhabit. The choice to include a creative project as a case study alludes to the synergetic relationship between theory and practice. One that is cyclical; one that speaks directly to the method of image generation for purposes of performance making that is being proposed, where the route between breath, body, emotion and image, maps a circular trajectory.